Regulation of cell signaling pathways by Schisandrin in different cancers: Opting for "Swiss Army Knife" instead of "Blunderbuss" - Lin, Xiukun; Attar, Rukset; Mobeen, Iqra; Yulaevna, Ishmuratova Margarita; Aras, Aliye; Butt, Ghazala; Farooqi, Ammad Ahmad (Cellular and Molecular Biology, 2021)
There has been an exponential growth in the field of molecular oncology and cutting-edge research has enabled us to develop a better understanding of therapeutically challenging nature of cancer. Based on the mechanistic insights garnered from decades of research, puzzling mysteries of multifaceted nature of cancer have been solved to a greater extent. Our rapidly evolving knowledge about deregulated oncogenic cell signaling pathways has allowed us to dissect different oncogenic transduction cascades which play critical role in cancer onset, progression and metastasis. Pharmacological targeting of deregulated pathways has attracted greater than ever attention in the recent years. Henceforth, discovery and identification of high-quality biologically active chemicals and products is gaining considerable momentum. There has been an explosion in the dimension of natural product research because of tremendous potential of chemopreventive and pharmaceutical significance of natural products. Schisandrin is mainly obtained from Schisandra chinensis. Schisandrin has been shown to be effective against different cancers because of its ability to inhibit/prevent cancer via modulation of different cell signaling pathways. Importantly, regulation of non-coding RNAs by schisandrin is an exciting area of research that still needs detailed and comprehensive research. However, we still have unresolved questions about pharmacological properties of schisandrin mainly in context of its regulatory role in TGF/SMAD, SHH/GLI, NOTCH and Hippo pathways.